The performance of resistance, inductance, and capacitance handheld meters for determining moisture content of low-carbon fuels. (15th January 2017) - Davis, J.; Matovic, D.; Pollard, A.
Highlights: The performance of 9 handheld moisture meters on 7 low-carbon fuels was determined. The moisture content was increased by 5% intervals from a range of 0–60% (wet-basis). Performance varied by each meter, irrespective of the measurement technology. Performance improved if the sample was similar to the meters intended sample material. Abstract: The moisture content (MC) of a fuel is generally determined through gravimetric analysis where a sample is dehydrated in an oven over a period of approximately 24 h; the MC is then calculated by dividing the difference between the initial and final mass, by the initial mass. Handheld moisture meters offer the benefit of near-instantaneous measurements and should provide accurate and dependable results. The performance of nine moisture meters applied to seven low-carbon fuels (LCFs) was determined. The nine meters employed three measurement technologies: electrical conductance/resistance, electrical capacitance and electromagnetic inductance. The seven LCF samples considered were: shredded switchgrass, two batches of shredded wood, two batches of ragger tails and two batches of sanitary products. A moisture meter applicable for LCF should have a clear relationship between the actual MC and the measured MC, low variability, and be accurate within an absolute difference of 2%. Results indicated that none of the meters were suitable for use on LCF in general. It was not possible to identify a specific measurement technology that performed better for a certain LCF type from the results.